2018
DOI: 10.5007/2175-8069.2018v15n34p158
|View full text |Cite
|
Sign up to set email alerts
|

Glass ceiling em cargos de board e seu impacto no desempenho organizacional

Abstract: A pesquisa buscou identificar a incidência de glass ceiling nos cargos de board e seu impacto no desempenho organizacional das companhias brasileiras de capital aberto. Para sua operacionalização, adotou-se uma abordagem quantitativa, analisando-se 61 empresas com alto volume de negociação (IBrX 100) na Bolsa de Valores do Brasil. Constatou-se que os investidores institucionais não criam barreiras à valorização das empresas que promovem igualdade de gênero nos cargos de board, ou seja, que possuem mulheres que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(25 reference statements)
0
1
0
1
Order By: Relevance
“…Regarding the presence of women on boards, Almeida et al (2013) and Costa, Sampaio, and Flores (2019) found a negative relationship between the percentage of seats occupied by women and ROE, while Carvalhal da Silva and Margem (2015) showed that this relationship is not significant. Conversely, Magro, Carpes, Vergini, and Silva (2018) found a positive relationship. Regarding board size, Silveira et al (2003) showed that there is an optimal size (between five and six members), which is related to Tobin's q, while Condrige et al (2012) found a positive correlation between board size and firm performance.…”
Section: Integrated Analysis and Research Agendamentioning
confidence: 79%
“…Regarding the presence of women on boards, Almeida et al (2013) and Costa, Sampaio, and Flores (2019) found a negative relationship between the percentage of seats occupied by women and ROE, while Carvalhal da Silva and Margem (2015) showed that this relationship is not significant. Conversely, Magro, Carpes, Vergini, and Silva (2018) found a positive relationship. Regarding board size, Silveira et al (2003) showed that there is an optimal size (between five and six members), which is related to Tobin's q, while Condrige et al (2012) found a positive correlation between board size and firm performance.…”
Section: Integrated Analysis and Research Agendamentioning
confidence: 79%
“…Ademais, mesmo que as mulheres estejam preparadas, com alta experiência acadêmica e/ou profissional, estas são limitadas a determinados cargos e salários. (DAL MAGRO et al, 2018).…”
Section: Glass Ceiling E Segmentação Verticalunclassified